Modelling of stress-state-dependent ductile damage with gradient-enhancement exemplified for clinch joining - Friedlein, Johannes; Mergheim, Julia; Steinmann, Paul (Journal of the Mechanics and Physics of Solids, 2025)
A coupled finite plasticity ductile damage and failure model is proposed for the finite element simulation of clinch joining, which incorporates stress-state dependency and regularisation by gradient-enhancement of the damage variable. Ductile damage is determined based on a failure indicator governed by a failure surface in stress space. The latter is exemplary chosen as a combination of the Hosford–Coulomb and Cockcroft–Latham–Oh failure criteria for the high and low stress triaxiality range, respectively, to cover the wide stress range encountered in forming. Damage is coupled to elasto-plasticity to capture the damage-induced degradation of the stiffness and flow stress. This affects the material behaviour up to failure, thereby realistically altering the stress state. Consequently, especially for highly ductile materials, where substantial necking and localisation precede material fracture, the failure prediction is enhanced. The resulting stress softening is regularised by gradient-enhancement to obtain mesh-objective results. The analysis of a modified punch test experiment emphasises how the damage-induced softening effect can strongly alter the actual stress state towards failure. Moreover, the impact of successful regularisation is shown, and the applicability of the damage and failure model to clinch joining is proven.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Ductile damage; Failure; Finite plasticity; Gradient-enhancement; Stress-state dependency